Standardization of Human Diploid Fibroblast Cultivation: Trypsinization Procedure - Litwin, Jack (1971)
Human embryonic diploid lung fibroblasts were used to examine the influence of the trypsinizing procedure on the growth and adsorption of these cells. The best buffer for trypsinizing these cells was Hanks balanced salt solution containing 0.5% lactalbumin hydrolysate. Trypsinizing cells at 4 C gave better growth results than trypsinization at higher temperatures. The presence of antibiotics in the trypsin buffer increased the longevity of the cells. Cells initially trypsinized from tissue in phosphate-buffered saline without Ca(2+) or Mg(2+) and 0.33 m sucrose plus 10(−3)m Mg(2+) gave rise to better subsequent growth and adsorption than cells from tissue trypsinized in other buffers.